2016
DOI: 10.11113/umran2016.3n1.39
|View full text |Cite
|
Sign up to set email alerts
|

Intention to Contribute in Corporate Waqf: Applying the Theory of Planned Behaviour

Abstract: Corporate waqf has contributed a great change into the waqf system as a whole and been generally accepted as a way of waqf practice. However, the literature that discusses about the factors influencing people to contribute or involve in this practice is very limited. Prior to action, intention is taken place. Therefore, this study aims to examine the factors influencing people’s intention to contribute in corporate waqf, particularly to the employees of Majlis Agama Islam Wilayah Persekutuan (MAIWP), based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
29
3
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 18 publications
(19 reference statements)
8
29
3
3
Order By: Relevance
“…So far, people only understand that the waqf that can be done is waqf for immovable assets such as waqf for land, buildings, vehicles, and plants so that knowledge sharing is needed to increase public knowledge about current waqf developments. Hasbullah et al, (2016) explained that people who know cash waqf and desire to donate money will be an important factor that drives their behavior and actions in waqf money, and vice versa when they do not know cash waqf, there will be no encouragement. in him to do cash waqf (Hasbullah et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, people only understand that the waqf that can be done is waqf for immovable assets such as waqf for land, buildings, vehicles, and plants so that knowledge sharing is needed to increase public knowledge about current waqf developments. Hasbullah et al, (2016) explained that people who know cash waqf and desire to donate money will be an important factor that drives their behavior and actions in waqf money, and vice versa when they do not know cash waqf, there will be no encouragement. in him to do cash waqf (Hasbullah et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Hasbullah et al, (2016) explained that people who know cash waqf and desire to donate money will be an important factor that drives their behavior and actions in waqf money, and vice versa when they do not know cash waqf, there will be no encouragement. in him to do cash waqf (Hasbullah et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Ramayah, Rouibah, Gopi, & Rangel (2009) also asserted that attitude toward a behavior is the main contributing factor of behavioral intention. In the context of waqf giving behavior, Hasbullah (2016) and Shukor (2017) confirmed that attitude significantly influences intention to give waqf. Despite several researchers who believe attitude is a predictor of intention to give waqf, there are some scholars in the waqf field who are of the view that attitude may not be a sufficient factor that can influence the decision of an individual to give waqf.…”
Section: Attitudementioning
confidence: 97%
“…Thus, in the subsequent paragraphs, each of these identified constructs is discussed and hypotheses are also developed on each construct as they relate to waqf giving intention towards education sector. In the context of waqf, the TPB has been used by many waqf researchers (Osman, Mohammed, & Amin, 2014;Hasbullah, Khairi, & Aziz, 2016;Shukor, Anwar, Aziz, & Sabri, 2017;Zabri & Mohammed, 2018) and found that the TPB can explain waqf giving intention behavior. They concluded that TPB constructs could predict the intention of waqf giving behavior toward education sector.…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation